Analysis and Potential of Mlese Village in Realising Digital Literacy through the Smart Village Application in the Context of Implementing Educational Innovation - Anita Trisiana; Ama Farida Sari; Dony Prastyo (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: This community service program addresses rising socio-political issues in Klaten Regency, characterized by increasing violence and anarchic behavior. The focus is on Village Officials and the Youth Association of Mlese Village, as non-productive groups and pioneer agents of social change. The purpose is to strengthen the community's capacity to manage socio-cultural conflicts and promote social harmony. Purpose of the Study: The program aims to enhance digital literacy skills to help the target community filter information and manage socio-cultural conflicts, thereby fostering social harmony. Methods: The CIPP evaluation model (Context, Input, Process, Product) was employed, supported by the integration of the Smart Village Application (ASV) as an innovative digital platform aligned with Pancasila values. Activities included digital training workshops, mentoring, and collaborative village-based digital utilization practices. Results: The results show an 80% increase in digital literacy among participants, indicating a significant improvement in their ability to respond to online socio-cultural challenges. This initiative successfully reinforces sustainable community empowerment through technology and positions Mlese Village as a model for smart village development in Klaten Regency.